Assessment of the Primary Schools’ Physical Environment in Harion Municipality, Sarlahi - Mukhiya, Ram Babu; Mainali, Hari Lal (Chaturbhujeshwar Academic Journal, 2023)
The study assesses the physical environment of schools, highlighting their generally satisfactory but improvable state, emphasizing the pivotal role of school infrastructure in education, and the need for increased investment for an optimal learning environment. The aim of this study is to comprehensively assess the physical environment and infrastructure of schools in the context of Hariwan municipality, Nepal, encompassing aspects such as cleanliness, water and canteen facilities, toilet conditions, waste management, and playground safety. Method of this study is descriptive research design collecting data from 12 primary schools by using observation checklist to evaluate the physical environment. The study found that while the majority of schools in Hariwan municipality provide reasonably comfortable learning spaces, there is a strong case for increased investment in school infrastructure to ensure better physical conditions, including sanitation, water, canteen facilities, waste management, and playground safety, to enhance the overall educational experience and student well-being.